Endemic or regionally limited parasitic and fungal infections in haematopoietic stem-cell transplantation recipients: a Worldwide Network for Blood and Marrow Transplantation (WBMT) Review. Issue 4 (April 2023) - Muhsen, Ibrahim N; Galeano, Sebastian; Niederwieser, Dietger; Koh, Mickey B C; Ljungman, Per; Machado, Clarisse M; Kharfan-Dabaja, Mohamed A; de la Camara, Rafael; Kodera, Yoshihisa; Szer, Jeff; Rasheed, Walid; Cesaro, Simone; et al.
Summary: There is a scarcity of data on endemic and regionally limited fungal and parasitic infections in recipients of haematopoietic stem-cell transplantation (HSCT) outside western Europe and North America. This Worldwide Network for Blood and Marrow Transplantation (WBMT) Review is one of two papers aiming to provide guidance to transplantation centres worldwide regarding prevention, diagnosis, and treatment based on the currently available evidence and expert opinion. These recommendations were created and reviewed by physicians with expertise in HSCT or infectious disease, representing several infectious disease and HSCT groups and societies. In this paper, we review the literature on several endemic and regionally limited parasitic and fungal infections, some of which are listed as neglected tropical diseases by WHO, including visceral leishmaniasis, Chagas disease, strongyloidiasis, malaria, schistosomiasis, histoplasmosis, blastomycosis, and coccidioidomycosis.